Health-Related Quality of Life after Adolescent Fractures of the Femoral Shaft Stabilized by a Lateral Entry Femoral Nail - Thoralf Randolph Liebs; Anna Meßling; Milan Milosevic; Steffen Michael Berger; Kai Ziebarth (MDPI AG, 2022)
(1) Background: In adolescents, fractures of the femoral shaft that are not suitable for elastic-stable-intramedullary-nailing (ESIN), are challenging. We aimed to evaluate the health-related quality of life (HRQoL) and complications in adolescents treated with intramedullary rodding using the adolescent lateral trochanteric entry femoral nail (ALFN), and to assess if HRQoL was associated with additional injuries. (2) Methods: We followed-up on 15 adolescents with a diaphyseal femoral fracture who were treated with an ALFN from 2004 to 2017. Patients were asked to fill in a questionnaire that includes the iHOT, Peds-QL, and the Pedi-IKDC. (3) Results: The ALFN was used as a primary method of fixation in 13 patients, and as a fixation for failed ESIN in two cases. All 15 fractures healed radiographically. One distal locking screw broke. After a mean follow-up of 2.8 years, the mean iHOT-12 was 14.0 (SD 15.4), PedsQL-function was 85.7 (SD 19.3), PedsQL-social-score was 86.2 (SD 12.5), and the mean Pedi-IKDC was 77.2 (SD 11.3). In patients where the femoral fracture was an isolated injury, the HRQoL-scores were consistently higher compared with patients who sustained additional injures. (4) Conclusions: Treating diaphyseal fractures in adolescents with an ALFN resulted in good radiographic outcomes in all our cases. HRQoL, as measured by the iHOT, PedsQL, and Pedi-IKDC, was good to excellent; but it was consistently inferior in patients with additional injuries. These results suggest that the ALFN is a good alternative when patients are not suitable for ESIN, and that the HRQoL of adolescents who were treated with an ALFN is mainly influenced by the presence of additional injures, and less by the fracture of the femur itself.